Regional Buddhist Communities in Tang China and Their Social Networks: The Network of Master Fayun (?–766) - Sokolova, Anna (Religions, 2023)
This paper investigates the formation of monastic networks in Tang Dynasty (618–907) China, focusing primarily on the Buddhist traditions of Tiantai, Chan and Vinaya, which have yet to be explored as a series of related regional movements. Central to this effort is a dataset that documents over 2000 interactions between some 700 actors that were extracted from stelae inscriptions, monastic biographical collections, historical accounts, letters, and poems. The network data show two clear patterns in the organization of regional Buddhist communities: (1) individual actors bridged cliques of monastics and officials; (2) both monastics and officials contributed to network activities. To illustrate these two patterns, this paper focuses on the ego-network of Fayun 法雲 (?–766), a prominent Vinaya leader based in Jiangsu region, as an example of the formation and evolution of regional Buddhist communities in southern China. Degree centrality indicates that Fayun was one of the central figures in the southern Buddhist landscape of the early eighth century. By tracing his heterogeneous ties with prominent state officials, local authorities, and monastics affiliated with the Tiantai, Chan, and Vinaya traditions, this study outlines general patterns in the formation and legitimization of regional Buddhist communities in Tang China. All three traditions are revealed as intersecting social formations that were sustained through shared ties with local and nationally prominent bureaucrats.